The preventive potential of Citrullus vulgaris (Thunb.) seed extract on cafeteria diet, atherogenic diet-induced obesity, and formaldehyde/ Freund's adjuvant arthritis models in rats - Prasenjit Mondal; Megha Kulkarni; Rekhabai Thakur; Manukonda Kumar; Venu Kola (Shiraz University of Medical Sciences, 2021)
This present study was aimed to explore the anti obesity and anti arthritic activities of seed extracts of Citrullus vulgaris (Thunb) in cafeteria diet (CD), atherogenic diet (AD) induced obesity and Formaldehyde and Freund's adjuvant (FA) induced arthritis in experimental animals i.e. rats. The ethanolic and aqueous extracts were prepared by using soxhlet apparatus and maceration process respectively. Anti obesity activity of seed extracts of this plant was evaluated in CD and AD induced obesity and anti arthritic activity was evaluated in formaldehyde and FA induced arthritis in rats. Phytochemical studies with both ethanolic extract (ELSCV) and aqueous extract (AQSCV) revealed the presence of carbohydrates, proteins, flavonoids, saponins, fixed oils, glycosides and steroids. No mortality or behavioral abnormality recorded in mice at the highest dose level of 2000 mg/kg tested for LD50 studies. Both the extracts with medium and high doses exhibited a significant anti obesity activity by reducing the body weight, food intake, organ and fat pads weight and serum glucose, cholesterol, triglyceride, low density lipoproteins and very low density lipoprotein cholesterol levels with an increased high density levels in CD and AD induced obesity models in rats. Both extracts with medium and high doses exhibited a significant anti arthritic activity and reduced serum biochemical parameters in FA induced arthritis model in rats. The anti obesity and anti arthritic activities with extracts conformed the above mentioned activities because presence of flavonoids, saponins, fixed oils, steroids, alkaloids and glycosides.